How Much!? Determining the Cost of an Assignment in an Organic Chemistry Class. Issue 3 (3rd July 2019) - Kromer, John
ABSTRACT: Students in Organic Chemistry for Majors were required to write a paper as the culminating course assignment. Prior to completing this assignment, students could attend a library instruction session covering relevant databases and resources. Upon submission of their papers, bibliographies from 53 students were collected. Calculations were made to attempt a holistic account of costs associated with completing the assignment. Factors such as the cost of journals, databases, and librarian time were all included in the overall cost estimate, totalling $7, 189.22 for this single assignment.